Przyczyny zróżnicowania poziomu rozwoju gospodarczego w Polsce: The reasons for differences in the levels of economic development in Poland - Szarek, Stanisław (Management and Administration Journal, 2021)
The article explains the reasons for differences between the economic development of Polish regions and the delay in development between Polish "A" and the Polish "B" regions. It is assumed that the level of economic development is determined by the number of people living in the region. This factor has an impact on the growth of labour productivity, and accelerates the accumulation of wealth in this region. However, the increase in population density can only take place under conditions of people access to adequate amounts of food. It is hypothesized that more food per unit area was produced in regions where the soil contained higher amounts of heavy metals. This is possible because the occurrence of a hormetic effect that is superior to other yielding factors. Crop yields on these soils are significantly higher than those in soils with lower levels of these metals. Based on empirical research it is determined that since the industrial revolution, the eastern region of our country, called Poland "B" could be delayed in the economic development of the region in relation to the West - Polish "A", for about 40 years.